The impact of mesh structural design on nonlinear numerical simulation of geo‐structure: A seismic analysis. Issue 5 (17th July 2020) - Namdar, Abdoullah
Abstract: The strain energy is one of the significant factors in geo‐structure nonlinear analysis. The design quality in geotechnical earthquake engineering associates with the accuracy of the numerical simulation and the high quality of the seismic response prediction. In this study, the embankment‐subsoil Models A and B are modeled with the same geometry and two different meshes. To predict the strain mechanism of the embankment‐subsoil model, the hexahedral and tetrahedral meshes are used in nonlinear numerical simulation. To control the quality of the numerical simulation, the statistical analysis was made. The results of the statistical analysis illustrate that mesh shape governs the accuracy of the numerical simulation. The finding of this study improves the simulation of strain mechanism in embankment‐subsoil seismic analysis.